Evaluasi Kompetensi Guru Bahasa Indonesia Berbasis APKG: Studi Kasus Tayangan Video Youtube - Antonius Nesi; Muhamad Haryanto; Wagiran Wagiran (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2023)
This study aims to evaluate the teaching competence of Bahasa Indonesia teachers using the APKG-2 evaluation tool. This research is classified as a case study with limited data sources, namely 4 (four) learning video shows on the Youtube channel. In line with that, this research is also called ex post facto research with a descriptive evaluation approach. As a descriptive evaluation study, at the data collection stage the researcher used the APKG-2 instrument. After the data was collected, the researcher processed and analyzed the data using descriptive statistical analysis techniques. The average acquisition of the assessment in each aspect of the assessment is used by researchers to evaluate by interpreting and interpreting the data. The results of this study indicate two things. First, there are two videos, namely video 1 which is related to thematic learning focused on Bahasa Indonesia in lower grade of Elementary Schools and video 3, namely learning Bahasa Indonesia in Junior High Schools which can be categorized as Good. Meanwhile, video 2 relating to thematic learning with a focus on Bahasa Indonesia in high grade of Elementary Schools and video 4 relating to learning Bahasa Indonesia in Senior High School can be categorized as Enough. Second, based on the results of the notes in the evaluation column, the researcher noted several important things that Indonesian language teachers should pay attention to, namely apperception and delivery of learning objectives that must be effective in opening activities, feedback, interaction, use of learning methods and media that must be in harmony with the learning materials in the class, core activities, as well as the importance of reflection on closing activities.